2018
DOI: 10.1007/s00209-018-2120-3
|View full text |Cite
|
Sign up to set email alerts
|

Equivariant quantum cohomology of the odd symplectic Grassmannian

Abstract: The odd symplectic Grassmannian IG :" IGpk, 2n`1q parametrizes k dimensional subspaces of C 2n`1 which are isotropic with respect to a general (necessarily degenerate) symplectic form. The odd symplectic group acts on IG with two orbits, and IG is itself a smooth Schubert variety in the submaximal isotropic Grassmannian IGpk, 2n`2q. We use the technique of curve neighborhoods to prove a Chevalley formula in the equivariant quantum cohomology of IG, i.e. a formula to multiply a Schubert class by the Schubert di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In this section, we briefly introduce the odd symplectic Grassmanian and some basic properties of its cohomology ring. We refer to for details; we follow closely the exposition from .…”
Section: Preliminariesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we briefly introduce the odd symplectic Grassmanian and some basic properties of its cohomology ring. We refer to for details; we follow closely the exposition from .…”
Section: Preliminariesmentioning
confidence: 99%
“…Unlike the homogeneous case, these numbers might be negative in general. For instance, using Pech's quantum Pieri rule to multiply [X(λ)][X(i)] in the case of the odd symplectic Grassmannian of lines IG (2,2n+1), one obtains in QH false( IG (2,5)false), [X(3,1)][X(2,1)]=1[X(3,2)]+;[X(3,1)][X(3,1)]=q[X(0)]+.For arbitrary k, the second and third authors found a Chevalley formula calculating [X(1)][X(λ)] in the equivariant quantum cohomology ring, and proved that this formula gives a recursive algorithm to calculate all the other structure constants (see ). The nonequivariant rule was also found in the recent paper .…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations